Discursive Strategies on Ridwan Kamil’s Status Update: a Critical Discourse Analysis - Yudhy Purwanto (Humaniora, 2017)
The research was aimed to know the impact of a written expression through social media toward the people who read it. The analysis was performed in accordance with the theories of strategy, discourse analysis, and critical discourse analysis put by Wodak and Meyer (2001) and Renkema (2009), and the theories of internet and language by Crystal (2004). The data were taken from the page of Ridwan Kamil, Mayor of Bandung in that social media. The research needed to see the strategy in his status update (written expression). From the Critical Discourse Analysis (CDA) point of view, it can be understood the way people transfer their ideas and thoughts showed their power and influenced the people through some certain strategies. The results of the research show (1) all strategies are used in his status update, namely the referential/nomination, the predication, the argumentation, the perspectivation and the intensification strategies, (2) there are always some implicit and explicit intentions that are shared through the status update, and (3) there are some certain aspects that affect the readers of the status update.